Pengaruh Dukungan Sosial terhadap Kepatuhan Lansia dalam Mengikuti Program Posyandu Lansia - Rasyid, Djusmadi; Mustarin, Yanti; Suardi, Vivi Adriana; Jukarnain, Jukarnain; Mulia, Madepan (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Posyandu (Integrated Health Post for the Elderly) is a preventive and promotive health service aimed at improving the quality of life of the elderly. However, attendance rates for the elderly are still relatively low. One factor influencing elderly compliance is social support from family, peers, and the surrounding environment. Objective: To determine the effect of social support on elderly compliance in participating in the Posyandu program. Methods: This study used a quantitative analytical design with a cross-sectional approach. A sample of 92 elderly people was selected using a purposive sampling technique in the working area of Community Health Center X. The instrument used was a social support and compliance questionnaire, which had been tested for validity and reliability. Data analysis was performed using binary logistic regression. Results: The majority of respondents (71.7%) had high social support, and 65.2% of elderly people were classified as compliant in attending Posyandu. Statistical tests showed that social support significantly influenced elderly compliance (p = 0.001; OR = 3.45). Conclusion: Social support significantly influences elderly compliance in participating in Posyandu activities. Recommendation: Enhancing the role of families and cadres in providing emotional, informational, and practical support is crucial for increasing elderly participation.